2019
DOI: 10.1021/acs.jced.9b00607
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of the Nonaqueous and Aqueous Mixtures of Methyldiethanolamine and Monoethylene Glycol at Temperatures from 283.15 to 353.15 K

Abstract: Nonaqueous and aqueous mixtures of methyldiethanolamine and monoethylene glycol form promising absorbents for the combined hydrogen sulfide removal and hydrate control, necessary in natural gas processing. In this direction, the density and viscosity of the binary and ternary systems were measured and modeled in the temperature range of T = 283.15−353.15 K and at ambient pressure. Excess molar volumes and viscosity deviations from ideality were also calculated. The water content varied from 5 to 50 wt % and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
3
8
0
Order By: Relevance
“…For density modeling, Pinto and Knuutila demonstrated good agreement between the densities calculated from the NRTL-DVOL model and those of experimental data for amine aqueous solutions or amine/amine/water mixtures. Then, Skylogianni et al reported the ability of NRTL-DVIS and NRTL-DVOL models to accurately correlate the viscosities and densities in their amine/glycol/water systems, a ternary system similar to ours. The results in density modeling for binary and ternary systems are less than 0.4 and 0.3%, respectively.…”
Section: Introductionsupporting
confidence: 56%
“…For density modeling, Pinto and Knuutila demonstrated good agreement between the densities calculated from the NRTL-DVOL model and those of experimental data for amine aqueous solutions or amine/amine/water mixtures. Then, Skylogianni et al reported the ability of NRTL-DVIS and NRTL-DVOL models to accurately correlate the viscosities and densities in their amine/glycol/water systems, a ternary system similar to ours. The results in density modeling for binary and ternary systems are less than 0.4 and 0.3%, respectively.…”
Section: Introductionsupporting
confidence: 56%
“…Solubility of CO 2 in MEG from Experiments and MC Simulations. Densities of pure MEG were computed using MC simulations in the NPT ensemble at P = 1 bar and at T = 333.15 K and T = 353.15 K. In Table 3, densities (reported in units of kg/m 3 ) from simulations are compared to experimental values from the work of Skylogianni et al 13 Table 3 shows that when using the TraPPE-UA force field, simulations underpredict the densities of MEG. The differences between experiments and simulations are around 5%.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of heat of absorption data was not performed because they are not relevant to this study. After each injection and after equilibrium is attained in the CO 2 cylinders, these cylinders have to be refilled with CO 2 from the wall (12) through opening of the valve (13). After achieving equilibrium in both cylinders and in the stirred cell, the next injection is performed and the process is repeated until the reactor approaches the maximum operational pressure of 6 bar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties of absorbents have a significant role in the design of gas–liquid contactors . For example, viscosity and density are useful in calculating the kinetic parameters, tray and column diameters in absorption units, packing height, and pumping energy requirements. , The vapor–liquid equilibrium data are important in solvent screening and development of theoretical models for simulation of CO 2 absorption plants . Absorption heat is one of the key parameters in determining the energy consumption by the reboiler for solvent regeneration …”
Section: Introductionmentioning
confidence: 99%